"For Gorsake, Stop Laughing: This is Serious!"—Australia's Fragile Cartooning Archive. Issue 1 (2nd January 2023) - Phiddian, Robert; Brookes, Stephanie; Foyle, Lindsay; Scully, Richard
ABSTRACT: Stan Cross's "For gorsake, stop laughing: this is serious!" ( Smith's Weekly, 1933) is the symbol and bellwether of the Australian cartooning tradition. It is often lionised as a national treasure, but its archival history has been perilous in a way that shows a lack of care amounting almost to national negligence. The original of this most famous cartoon of the Depression era was lost for 80 years before being rediscovered in 2014, and this article notes for the first time that Trove Newspapers lacks a record of its initial publication. We use this troubled material history of one significant cartoon to raise a range of issues about the quality and purpose of collecting and presenting Australian cartoons as a resource for Australian studies in fields ranging from media and humour studies to cultural and political history.